5.25.1 Problems 1 to 100

Table 5.1099: Second order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

149

\[ {}y^{\prime \prime }+4 y = 0 \]

215

\[ {}y^{\prime \prime }-y = 0 \]

216

\[ {}y^{\prime \prime }-9 y = 0 \]

217

\[ {}y^{\prime \prime }+4 y = 0 \]

218

\[ {}y^{\prime \prime }+25 y = 0 \]

219

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

220

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

221

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

222

\[ {}y^{\prime \prime }-3 y^{\prime } = 0 \]

223

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

224

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

225

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

226

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

234

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

235

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

236

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

237

\[ {}2 y^{\prime \prime }+3 y^{\prime } = 0 \]

238

\[ {}2 y^{\prime \prime }-y^{\prime }-y = 0 \]

239

\[ {}4 y^{\prime \prime }+8 y^{\prime }+3 y = 0 \]

240

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

241

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

242

\[ {}6 y^{\prime \prime }-7 y^{\prime }-20 y = 0 \]

243

\[ {}35 y^{\prime \prime }-y^{\prime }-12 y = 0 \]

263

\[ {}y^{\prime \prime }-2 y^{\prime }-5 y = 0 \]

265

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

271

\[ {}y^{\prime \prime }-4 y = 0 \]

272

\[ {}2 y^{\prime \prime }-3 y^{\prime } = 0 \]

273

\[ {}y^{\prime \prime }+y^{\prime }-10 y = 0 \]

274

\[ {}2 y^{\prime \prime }-7 y^{\prime }+3 y = 0 \]

275

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

276

\[ {}y^{\prime \prime }+5 y^{\prime }+5 y = 0 \]

277

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

278

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

279

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 0 \]

291

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 0 \]

292

\[ {}9 y^{\prime \prime }+6 y^{\prime }+4 y = 0 \]

293

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

309

\[ {}y^{\prime \prime }+2 i y^{\prime }+3 y = 0 \]

310

\[ {}y^{\prime \prime }-i y^{\prime }+6 y = 0 \]

311

\[ {}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y \]

530

\[ {}x^{\prime \prime }+4 x = 0 \]

531

\[ {}x^{\prime \prime }+9 x = 0 \]

532

\[ {}x^{\prime \prime }-x^{\prime }-2 x = 0 \]

533

\[ {}x^{\prime \prime }+8 x^{\prime }+15 x = 0 \]

541

\[ {}x^{\prime \prime }+6 x^{\prime }+25 x = 0 \]

807

\[ {}y^{\prime \prime }-y = 0 \]

808

\[ {}y^{\prime \prime }-9 y = 0 \]

809

\[ {}y^{\prime \prime }+4 y = 0 \]

810

\[ {}y^{\prime \prime }+25 y = 0 \]

811

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

812

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

813

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

814

\[ {}y^{\prime \prime }-3 y^{\prime } = 0 \]

815

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

816

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

817

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

818

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

823

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

824

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

825

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

826

\[ {}2 y^{\prime \prime }+3 y^{\prime } = 0 \]

827

\[ {}2 y^{\prime \prime }-y^{\prime }-y = 0 \]

828

\[ {}4 y^{\prime \prime }+8 y^{\prime }+3 y = 0 \]

829

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

830

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

831

\[ {}6 y^{\prime \prime }-7 y^{\prime }-20 y = 0 \]

832

\[ {}35 y^{\prime \prime }-y^{\prime }-12 y = 0 \]

845

\[ {}y^{\prime \prime }-4 y = 0 \]

846

\[ {}2 y^{\prime \prime }-3 y^{\prime } = 0 \]

847

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 0 \]

848

\[ {}2 y^{\prime \prime }-7 y^{\prime }+3 y = 0 \]

849

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

850

\[ {}y^{\prime \prime }+5 y^{\prime }+5 y = 0 \]

851

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

852

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

853

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 0 \]

854

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 0 \]

855

\[ {}9 y^{\prime \prime }+6 y^{\prime }+4 y = 0 \]

856

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

857

\[ {}y^{\prime \prime }-2 i y^{\prime }+3 y = 0 \]

858

\[ {}y^{\prime \prime }-i y^{\prime }+6 y = 0 \]

859

\[ {}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y \]

862

\[ {}\frac {x^{\prime \prime }}{2}+3 x^{\prime }+4 x = 0 \]

863

\[ {}3 x^{\prime \prime }+30 x^{\prime }+63 x = 0 \]

864

\[ {}x^{\prime \prime }+8 x^{\prime }+16 x = 0 \]

865

\[ {}2 x^{\prime \prime }+12 x^{\prime }+50 x = 0 \]

866

\[ {}4 x^{\prime \prime }+20 x^{\prime }+169 x = 0 \]

867

\[ {}2 x^{\prime \prime }+16 x^{\prime }+40 x = 0 \]

868

\[ {}x^{\prime \prime }+10 x^{\prime }+125 x = 0 \]

929

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

1249

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

1250

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

1251

\[ {}6 y^{\prime \prime }-y^{\prime }-y = 0 \]

1252

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

1253

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

1254

\[ {}4 y^{\prime \prime }-9 y = 0 \]

1255

\[ {}y^{\prime \prime }-9 y^{\prime }+9 y = 0 \]

1256

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

1257

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

1258

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 0 \]